南极普里兹湾及其邻近海域表层水镭同位素的分布及应用 - 陈倩娜; 任春燕; 李琦; 李敬轩; 贾仁明; 郑敏芳; 邱雨生; 陈敏 (2015)
中国第27次南极科学考察期间(2010年12月30日至2011年1月16日),对普里兹湾及其邻近海域表层海水进行了226rA和228rA的分析,结果表明:226rA和228rA比活度的变化范围分别为1.47—2.43bQ/M3和0.17—0.45bQ/M3,平均值分别为2.13bQ/M3和0.29bQ/M3,228rA/226rA)A.r.(228rA与226rA的活度比)的变化范围为0.08—0.20,平均值为0.14。根据盐度和226rA的质量平衡方程,计算出研究海域表层水中冰融水、南极夏季表层水和普里兹湾中深层水的份额。研究海域表层水中温度、盐度、226rA、228rA、228rA/226rA)A.r.和冰融水份额的空间分布显示,在埃默里冰架前沿海域,西侧海域较东侧海域具有低温、高盐、高226rA、低228rA、低228rA/226rA)A.r.、低冰融水份额的特征,证实埃默里冰架下水体东进西出的运动规律。根据埃默里冰架前沿东、西侧水体228rA/226rA)A.r.的差异,估算出埃默里冰架下表层水体东进西出所经历的时间为1.85A。此外,在普里兹湾湾口中部海域(66.5—67.5°S,72°—74°E),观察到次表层水的上升通风作用,该区域较高的228rA含量和228rA/226rA)A.r.证明这些表层水体并非来自湾外绕极深层水的上涌,而可能来自湾内埃默里冰架输出水体。 226Ra and 228 Ra in surface water in the Prydz Bay Antarctica and its adjacent sea areas were measured during the 27 th China Antarctic Research Expedition(from December 30, 2010 to January 16, 2011).Our results show that 226 Ra and 228 Ra activity concentrations ranged from 1.47 to 2.43Bq/m3 and from 0.17 to 0.45Bq/m3, in average of 2.13Bq/m3 and 0.29Bq/m3, respectively.228Ra/226Ra)A.R.varied from 0.08 to 0.20 in average of 0.14.Based on mass balance of salinity and 226 Ra, fractions of three components, i.e.ice-melted water, Antarctic summer surface water, and the Prydz Bay deep water, were calculated.Along the front of the Amery ice shelf, characteristics of low temperature, high salinity, high 226 Ra, low 228 Ra, low 228Ra/226Ra)A.R.and low fraction of the ice-melted water were observed in the western region compared to the eastern region, indicating that waters flow into the ice shelf in the eastern region and exit in the western region.The elapsed time for surface water transport from the eastern to the western was estimated as 1.85 a according to the change of surface 228Ra/226Ra)A.R.In addition, ventilation of sub-surface water was observed in the central mouth of the Prydz Bay(66.5°—67.5°S, 72—74°E).Relatively high 228 Ra and 228Ra/226Ra)A.R.in the central mouth of the Prydz Bay suggested that these surface waters came from the exported waters from the western Amery ice shelf, not from the upwelling of circumpolar deep water. 南北极环境综合考察与评估专项;CHINARE2014-01-04-03号;CHINARE2014-04-01-06号; 国家自然科学基金杰出青年基金项目;41125020号; 厦门大学海洋科学国家人才基地项目;2013C01号